Diaboliche, maledette e disperate Le donne nei processi per stregoneria (secoli XIV-XVI) - Corsi, Dinora (Biblioteca di storia, 2013)
In a time, ours, in which historiography prefers to measure itself with witchcraft as a judicial phenomenon, or with the men who personally led the persecution, or even with the demonological treatises that greatly influenced witch hunters, this book focuses instead on the victims. Women accused of witchcraft are the protagonists of the trials initiated between the late Middle Ages and the early modern age: that was the time when the great witch hunt was unleashed in Europe. The profiles of the alleged witches, even if drawn by their judges, emerge from these pages in all their changeability and drama: women that are reluctant to plead guilty to unspoken crimes, marked by stubborn silence, surrendered to the full confession of every wickedness extorted by torture.